PAIN INTENSITY AND PAIN INTERFERENCE AMONG TRAUMA PATIENTS: A LITERATURE REVIEW - Deya Prastika; Luppana Kitrungrote; Jintana Damkliang (Belitung Nursing Journal, 2016)
Background: The incidence of trauma has been high and has gained attention worldwide. The energy involved in trauma results in specific tissue damage. Such tissue damage generally leads to pain. The high pain intensity possibly is consequence of trauma due to transfer energy to the body from external force and absorbed in wide area. This pain affected patients’ physical and psychological function, in which well known as pain interference. Objective: The aim of this review is to describe the pain intensity and pain interference among trauma patients. Method: A systematic search of electronic databases (CINAHL, ProQuest, Science Direct, and Google scholar) was conducted for quantitative and qualitative studies measuring pain intensity and pain interference. The search limited to hospitalized trauma patients in adult age. Results: The search revealed 678 studies. A total of 10 descriptive studies examined pain intensity and pain interference and met inclusion criteria. The pain intensity and pain interference were assessed using Brief Pain Inventory (BPI). Pain intensity of hospitalized trauma patients were moderate to severe. These including 6 studies in orthopedic trauma, one study in musculoskeletal, two in studies in combinational between orthopedic and musculoskeletal, and two studies in burn injury. Moreover, the patients also reported pain was relentless & unbearable. In accordance, data showed that pain interference was moderate to severe from six studies. These studies result in vary of functional interference. However, those studies examined pain interference on sleep, enjoyment of life, mood, relationship with other, walking, general activity, and walking. Conclusion: The evidence from 10 studies included in this review indicates that hospitalized trauma patients perceived moderate to severe pain intensity and pain interference. Further research is needed to better evaluate the pain of hospitalized trauma patients.